Veterinary Technicians and Occupational Burnout - Kogan, Lori R.; Wallace, Jean E.; Schoenfeld-Tacher, Regina; Hellyer, Peter W.; Richards, Madeline (Frontiers in Veterinary Science, 2020)
Burnout and compassion fatigue are common conditions affecting health care providers. Unique occupational conditions in veterinary medicine make technicians especially susceptible to burnout. A total of 1642 practicing veterinary technicians completed an anonymous online survey comprised of demographic questions, the Maslach Burnout Inventory - General Survey (MBI-GS) and the Stanford Professional Fulfillment Index (PFI). The mean average MBI-GS scores were emotional exhaustion (EE) scale: x = 3.47 (SD = 1.44); cynicism (CY) scale: x=2.55 (SD = 1.58); and professional efficacy (PE) scale: x = 4.82 (SD = 0.95). Over half of participants (862/1479, 58.3%) had EE scores over the 3.0 threshold for burnout. On the PFI, the total score for the 10 burnout questions was x=1.54 (SD = 0.75), which is above the 1.33 cutoff for burnout. The mean score of 2.26 (SD = 0.81) on the professional fulfillment scale is also indicative of burnout. The relationship between enabling resources and scores on each MBI-GS scale was analyzed. Schedule control was the most significant predictor of lower EE scores. The perception of adding value to the practice was associated with lower scores on the CY scale and higher scores on the PE scale. Given the correlation between burnout and environmental factors, veterinary practices are encouraged to explore non-monetary mechanisms for enhancing job satisfaction. This includes giving technicians greater control over their schedules, recognizing their contributions to the team, and providing opportunities for professional development. From a morale standpoint, destigmatizing the dirty work done by technicians can also help combat burnout among veterinary technicians.